PENGEMBANGAN PRODUK OLAHAN KELAPA SEBAGAI SEKTOR UNGGUL DI DESA BABABULO KABUPATEN MAJENE - Rahmi, Mujiba; Syafruddin, Reni Fatmasari; Arwati, Sitti (AgriMu, 2023)
Coconut plants are one of the plants that are very useful in rural economic life, one of which is in Bababulo Village, Majene Regency. All parts of the coconut tree can be used to meet human needs. This study aims to determine the process of making coconut into processed coconut oil or virgin coconut oil (VCO) and to determine the income of the Anjoro Tuo business group. The informant in this study is the Anjoro Tuo business group. The analytical tool used is descriptive qualitative. The Qualitative Method is a descriptive research, by collecting data through observation and conducting direct interviews and taking documentation. The results showed that VCO processing was carried out by the community in Bababulo Village, Majene Regency, namely the coconut milk fermentation method which started by removing the coconut fiber, splitting the coconut, gouging out the coconut meat, cleaning the coconut meat, the grating process, the squeezing process, the coconut milk fermentation, the cooking process, and the packaging. . The total income value of the Anjoro Tuo Business group in Bababulo Village, Majene Regency from the sale of VCO is Rp. 31.140,000/month. Keywords : superior product, business group, vco, income